People at a y-Walk party - Unknown:::Creator::::::::::::
Photograph shows a group of men and women dressed in nice clothing sitting at a table with drinks, possibly at D.B. Cooper's. They appear to be outside and may be at a party for the y-Walk event. Most of the women have visible red and white y-Walk stickers on their clothes and there are probably y-Walk balloon bouquets in the background. One women is gesturing with a thumbs up with both hands.